Software engineering : challenges and solutions : results of the XVIII KKIO 2016 Software Engineering Conference 2016 held at September 15-17 2016 in Wroclaw, Poland /: challenges and solutions : results of the XVIII KKIO 2016 Software Engineering Conference 2016 held at September 15-17 2016 in Wroclaw, Poland. ([2017]) - Unknown
No abstract available